Efficient silver nanoparticles deposition method on DBD plasma-treated polyamide 6, 6 for antimicrobial textiles. (December 2018) - Ribeiro, A I; Senturk, D; Silva, K S; Modic, M; Cvelbar, U; Dinescu, G; Mitu, B; Nikiforov, A; Leys, C; Kuchakova, I; Vanneste, M; Heyse, P; et al.
Abstract: Several methods for silver nanoparticles (AgNPs) deposition on dielectric barrier discharge (DBD) plasma treated and not treated polyamide 6, 6 fabric were tested for the production of durable antibacterial textiles. Ultrasound-assisted, dip-coating, exhaustion at 70°C and spray deposition methods were applied. The treated fabrics were analysed in terms of coating uniformity, plasma effect, nanoparticles concentration onto the fabrics and nanoparticles release. Scanning electron microscope (SEM), energy dispersive X-ray (EDX), atomic absorption spectroscopy (AAS), inductively coupled plasma optical emission spectrometry (ICP-OES) and reflectance spectroscopy(%R) were performed. In the fabrics impregnated with AgNPs by dip coating or spray methods there are no significant differences in the plasma treated and untreated samples. Ultrasound tip and exhaustion at 70°C presented higher AgNPs loading. Better AgNPs distribution, higher concentration and less agglomeration were observed in the plasma treated samples and an improved controlled release as well. The plasma treated fabrics with AgNPs deposited with the ultrasound method showed the highest concentration of nanoparticles onto the fabrics as well as the lowest NPs agglomeration. However, this deposition is limited to certain areas of the fabric, the samples were not uniform. The exhaustion method showed the best equilibrium between the NPs distribution and state of agglomeration.